2023
DOI: 10.1021/acs.macromol.3c01096
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of a Polyelectrolyte Chain at Dielectric Surfaces: Effects of Surface Charge Distribution and Relative Dielectric Permittivity

Ruochao Wang,
Valeriy V. Ginzburg,
Jian Jiang
et al.

Abstract: The characteristics of a surface, such as surface charge distribution and permittivity, play significant roles in polyelectrolyte (PE) adsorption. However, systematic studies of these effects are rare in the literature. In this work, we employ a local lattice Monte Carlo algorithm to investigate the effects of dielectric contrast, charge fraction, and surface charge density on the adsorption behavior of a PE chain onto surfaces with different charge distributions. We consider three surface charge distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
0
0
Order By: Relevance
“…Existing studies have largely focused on how repulsive image charges and finite potential differences influence polyelectrolyte adsorption behavior and energy storage. For example, Monte Carlo simulations by Wang et al 67 have elucidated how repulsive image charges can either enhance or penalize polyelectrolyte adsorption depending on the polyelectrolyte charge fraction and surface charge distribution. MD efforts by Bagchi et al 68 have revealed that repulsive image charges give rise to enhanced energy storage in polyelectrolyte EDLCs at low surface charge densities due to charge amplification.…”
Section: Image Charge Effects On Polyelectrolyte Adsorptionmentioning
confidence: 99%
“…Existing studies have largely focused on how repulsive image charges and finite potential differences influence polyelectrolyte adsorption behavior and energy storage. For example, Monte Carlo simulations by Wang et al 67 have elucidated how repulsive image charges can either enhance or penalize polyelectrolyte adsorption depending on the polyelectrolyte charge fraction and surface charge distribution. MD efforts by Bagchi et al 68 have revealed that repulsive image charges give rise to enhanced energy storage in polyelectrolyte EDLCs at low surface charge densities due to charge amplification.…”
Section: Image Charge Effects On Polyelectrolyte Adsorptionmentioning
confidence: 99%